THE AFFECTION OF INTERVIEWER SUPPORT ON ONE’S PERCEPTION AND PERFORMANCE IN AN ORAL PROFICIENCY INTERVIEW (Universitas Negeri Semarang, 2012)
This study examines the relationship of the support provided by the interviewers on the test-taker perception and performance. There are two levels of support investigated: High Supporting Behavior (HSB) and Low Supporting Behavior (LSB). Ten participants sat in two interviews with two different interviewers applying LSB and HSB condition each. All participants completed a perception questionnaire at the end of the interviews. Twenty interview scripts were computed to determine the participants’ actual performance in three categories: (1) fluency, (2) lexical resources and (3) grammar complexity. The results of the study reveals that there are effects on performance but not perception.